Teacher Absenteeism in Rural Indonesian Schools: A Dilemma - Mia Febriana; Yeni Karlina; Joko Nurkamto; Dewi Rochsantiningsih (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
The main problem which faced by rural Indonesian schools is teacher absenteeism which leads to low motivation students on teaching and learning process. The research aims to investigate the cause of teacher absenteeism in rural Indonesian schools. The participant of this research was the 4 pre-service teachers of SM-3T program who were sent to Sambas (Kalimantan Island), Maluku Barat Daya, Alor (East Nusa Tenggara), and Mamberamo (Papua). This research employs a narrative descriptive method. The techniques of data collection comprise questionnaire and in-depth interview. Furthermore, this study is supposed to contribute to the teacher professional development in the rural Indonesian schools.